The Meaning of ان تحار /Intihaar/ and ا س ت شهاد /Istisyhaad/ in Al-Jazeera Newspaper: A Semantic Pragmatic Review - Maulia Safitri Dewi; Apipudin Apipudin (Proceedings of AICS - Social Sciences, 2018)
This research is grounded on the use of the word انتحار/intihaar/ and استشهاد/istisyhaad/ in Al-Jazeera newspaper in order to express and describe the meaning of “death” in Arabic. Although both words have “death” as the meaning, both have different contexts and forms. Therefore, it is interesting to be studied semantically and pragmatically. This research applies qualitative method with descriptive approach. The data included in this study come from several news headlines from Al-Jazeera newspaper from 2013 until 2018. This research uses Critical Discourse Analysis theory from Norman Fairclough (1995). Once analysed, it can be compared that on the news which use the word انتحار/intihaar/ refers to the people whose deaths were caused by suicide. Whereas the news which use the word استشهاد/istisyhaad/ refers to the martyrs who in this context are Palestinians who struggle and fight against the colonizer (Israel) or in the dictionary is also called by the word jihad.Keywords:Al-Jazeera, critical discourse analysis, انتحار/intihaar/, استشهاد/istisyhaad/, Palestine